High-Performance Complementary Transistors and Medium-Scale Integrated Circuits Based on Carbon Nanotube Thin Films - Yang, Yingjun; Ding, Li; Han, Jie; Zhang, Zhiyong; Peng, Lian-Mao (ACS nano, 2017)
Solution-derived carbon nanotube (CNT) network films with high semiconducting purity are suitable materials for the wafer-scale fabrication of field-effect transistors (FETs) and integrated circuits (ICs). However, it is challenging to realize high-performance complementary metal-oxide semiconductor (CMOS) FETs with high yield and stability on such CNT network films, and this difficulty hinders the development of CNT-film-based ICs. In this work, we developed a doping-free process for the fabrication of CMOS FETs based on solution-processed CNT network films, in which the polarity of the FETs was controlled using Sc or Pd as the source/drain contacts to selectively inject carriers into the channels. The fabricated top-gated CMOS FETs showed high symmetry between the characteristics of n- and p-type devices and exhibited high-performance uniformity and excellent scalability down to a gate length of 1 μm. Many common types of CMOS ICs, including typical logic gates, sequential circuits, and arithmetic units, were constructed based on CNT films, and the fabricated ICs exhibited rail-to-rail outputs because of the high noise margin of CMOS circuits. In particular, 4-bit full adders consisting of 132 CMOS FETs were realized with 100% yield, thereby demonstrating that this CMOS technology shows the potential to advance the development of medium-scale CNT-network-film-based ICs.